2017
DOI: 10.1101/gad.295857.117
|View full text |Cite
|
Sign up to set email alerts
|

PHF6 regulates phenotypic plasticity through chromatin organization within lineage-specific genes

Abstract: Developmental and lineage plasticity have been observed in numerous malignancies and have been correlated with tumor progression and drug resistance. However, little is known about the molecular mechanisms that enable such plasticity to occur. Here, we describe the function of the plant homeodomain finger protein 6 (PHF6) in leukemia and define its role in regulating chromatin accessibility to lineage-specific transcription factors. We show that loss of Phf6 in B-cell leukemia results in systematic changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 95 publications
8
50
0
Order By: Relevance
“…In contrast to PHF3, ACTL6A and BRD2 were accumulating at laserinduced DNA lesions (Fig EV2B). Interestingly, another hit from our screen, the transcriptional regulator PHF6 (PHD finger 6), was found to be mutated in Börjeson-Forssman-Lehmann syndrome, which is a rare X-linked genetic disorder characterized by mental retardation, craniopharyngeal abnormalities, and hematological cancers [39][40][41][42][43][44]. This is in accordance with a recent study showing that BRD2 is recruited to nuclease-induced DSBs [38].…”
supporting
confidence: 91%
See 2 more Smart Citations
“…In contrast to PHF3, ACTL6A and BRD2 were accumulating at laserinduced DNA lesions (Fig EV2B). Interestingly, another hit from our screen, the transcriptional regulator PHF6 (PHD finger 6), was found to be mutated in Börjeson-Forssman-Lehmann syndrome, which is a rare X-linked genetic disorder characterized by mental retardation, craniopharyngeal abnormalities, and hematological cancers [39][40][41][42][43][44]. This is in accordance with a recent study showing that BRD2 is recruited to nuclease-induced DSBs [38].…”
supporting
confidence: 91%
“…Moreover, PHF6 localizes within the nucleolus, where it is important for the repression of ribosomal DNA transcription [46,47]. Mass spectrometry studies have indicated that PHF6 might be part of the NuRD complex, an ATP-dependent chromatin remodeler that also harbors histone deacetylation activity [42,43,50]. On that note, ribosomal RNA synthesis is inhibited after DNA damage, and this response is mediated by, besides PHF6, DNA-PK, and PARP1, factors promoting the repair of DSBs through NHEJ [48,49].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, this patient's tumour also carried a probable pathogenic truncating mutation in the transcription factor PHF6. Loss of function mutations in PHF6 have recently been implicated in leukemogenesis and lineage plasticity (Soto‐Feliciano et al , ). Although previously described in AML and T‐ALL, there are no prior studies that identify this mutation in B‐ALL.…”
Section: Laboratory Data Illustrating Lineage Plasticity From Diagnosmentioning
confidence: 99%
“…Although previously described in AML and T‐ALL, there are no prior studies that identify this mutation in B‐ALL. Most intriguing, Soto‐Feliciano et al () described a mouse model of phenotype plasticity in leukaemic cells from PHF6 ‐knockout mice induced by the oncogene BCR ‐ ABL1, further illustrating the importance of this transcription factor in navigating selection pressure.…”
Section: Laboratory Data Illustrating Lineage Plasticity From Diagnosmentioning
confidence: 99%